Mesenchymal Stem Cell Therapy of Pulmonary Fibrosis: Improvement with Target Combination. Issue 11 (November 2018) - Chuang, Hong-Meng; Shih, Tina Emily; Lu, Kang-Yun; Tsai, Sheng-Feng; Harn, Horng-Jyh; Ho, Li-Ing
Although the clinical application of new drugs has been shown to be effective in slowing disease progression and improving the quality of life in patients with pulmonary fibrosis, the damaged lung tissue does not recover with these drugs. Thus, there is an urgent need to establish regenerative therapy, such as stem cell therapy or tissue engineering. Moreover, the clinical application of mesenchymal stem cell (MSC) therapy has been shown to be safe in humans with idiopathic pulmonary fibrosis (IPF). It seems that a combination of MSC transplantation and pharmaceutical therapy might have additional benefits; however, the experimental design for its efficacy is still lacking. In this review, we provide an overview of the mechanisms that were identified when IPF was treated with MSC transplantation or new drugs. To maximize the therapeutic effect, we suggest that MSC transplantation is combined with drug application for synergistic effects. This review provides clinicians and scientists with the most efficient medical options, in the hope that this will spur on future research and lead to an eventual cure for this disease.